Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.accounts.6b00164
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Mycobacterial Glycans: Furanosides and Beyond

Abstract: ConspectusThe cell surface (or cell wall) of bacteria is coated with carbohydrate (or glycan) structures that play a number of important roles. These include providing structural integrity, serving as a permeability barrier to extracellular compounds (e.g., drugs) and modulating the immune system of the host. Of interest to this Account is the cell wall structure of mycobacteria. There are a host of different mycobacterial species, some of which cause human disease. The most well-known is Mycobacterium tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…While great strides in thiourea catalysis are exemplified in the above mentioned reports, considerable challenges still remain in the employment of thiourea/urea catalysis on a broader scale in carbohydrate chemistry. The glycosyl donors employed in thiourea catalysis have remained in the pyranose realm and thiourea catalysis is rarely known to effectively catalyse glycosylations with donors bearing the furanose scaffold 33 36 . In fact, effective furanosylation protocols are scarce in catalysis 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…While great strides in thiourea catalysis are exemplified in the above mentioned reports, considerable challenges still remain in the employment of thiourea/urea catalysis on a broader scale in carbohydrate chemistry. The glycosyl donors employed in thiourea catalysis have remained in the pyranose realm and thiourea catalysis is rarely known to effectively catalyse glycosylations with donors bearing the furanose scaffold 33 36 . In fact, effective furanosylation protocols are scarce in catalysis 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The mycobacterial cell wall is a highly complex structure largely composed of carbohydrates and lipids. Major components are lipidated polysaccharides, like the mycolyl−arabinogalactan complex, essentially composed of galactofuranose (Gal f ) and arabinofuranose (Ara f ) [ 205 ]. In recent years, numerous efforts have been done to develop inhibitors of UDP-galactopyranose mutase (UGM), an enzyme essential for the growth and survival of this mycobacterium [ 206 , 207 , 208 , 209 , 210 , 211 , 212 ].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…Lipoarabinomannan (LAM) and related arabinogalactan (AG) are two major structural components of the M. tuberculosis cell wall. Previous studies revealed that LAM and especially its terminal oligosaccharide fragments, conjugated with proteins [7,10,19] or monophosphoryl lipid A [23], are attractive targets for the development of carbohydrate-based anti-TB vaccines [7,10,19,23,65,66].…”
Section: Tuberculosis (Tb) Which Is Caused By the Pathogenic Bacterimentioning
confidence: 99%